(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This study focuses on the recycling of agricultural and industrial wastes, specifically wheat straw ash (WSA) and bamboo wood ash (BWA), in cement production to promote sustainable and environmentally friendly concrete. The mechanical properties of WSA and BWA are investigated through tests measuring compressive strength, flexural strength, and split tensile strength of concrete. Different percentages of WSA and BWA (5%, 10%, 15%, and 20% by weight of cement) are used as partially replacement materials in the concrete mix. The experimental results indicate a reduction in the strength performance of concrete when WSA and BWA are individually used as supplementary cementitious materials at various curing periods (7, 28, 56, and 90 days). The primary objective of this study is to examine the impact of WSA and BWA on the mechanical properties of concrete for the purpose of sustainable development. The heavy use of energy and raw materials in traditional cement manufacture leads to a significant release of carbon dioxide into the atmosphere, which contributes to environmental pollution and greenhouse gas emissions. The environmental impact of cement production can be minimised by using WSA and BWA as cementitious materials in concrete. This is a successful strategy for reducing the damaging consequences of cement production on the environmentWSA and BWA can be used as cementitious materials in concrete to lessen the negative environmental effects of cement manufacture. This is a practical method for reducing the damaging environmental effects of cement manufacture.